Nurse-led weaning protocols—a systematic review and meta-analysis - Wang, Yingying; Wang, Yan; Gu, Su; Zhu, Liqun; Jia, Ruixiao; Tan, Min; Ma, Shaoyong (Frontiers in Medicine, 2025)
BackgroundResearch has demonstrated that protocol-directed weaning shortens the duration of mechanical ventilation (MV). Nurse-led weaning protocols have also been suggested to reduce MV duration in patients. Nevertheless, their implementation in mechanically ventilated patients is not widespread, and their clinical effectiveness remains uncertain.AimThis study aimed to evaluate the effectiveness of nurse-led weaning protocols compared to physician-led weaning in mechanically ventilated patients.MethodsEleven electronic databases (PubMed, Embase, Cochrane Library, CINAHL, EBSCO, Scopus, Web of Science, Sino Med, CNKI, VIP, and Wanfang) were systematically searched from their inception to January 20, 2024. Two researchers conducted a literature search and data extraction independently. We performed all statistical analyses using RevMan 5.1. The certainty of evidence was assessed using the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) profiler Guideline Development Tool.ResultsOur analysis included a total of six relevant studies. The analysis of pooled data revealed that nurse-led weaning protocols were associated with a significant reduction in the duration of MV (MD = −1.78 days, 95% confidence interval (CI) = −3.08 to −0.48, I2 = 82%, and p = 0.007; five studies; moderate quality), length of stay (LOS) in the intensive care unit (ICU) (MD = −2.04 days, 95% CI = −2.65 to −1.44, I2 = 0%, and p < 0.00001; five studies; moderate quality), and LOS (MD = −2.54 days, 95% CI = −3.95 to −1.14, I2 = 0%, and p = 0.0004; three studies; low quality). Furthermore, nurse-led weaning protocols were associated with a reduced incidence of ventilator-associated pneumonia (VAP) (OR = 0.54, 95% CI = 0.31 to 0.96, I2 = 0%, and p = 0.03; 2 studies; moderate quality).ConclusionCurrent evidence indicates that nurse-led weaning protocols have the potential to decrease the duration of MV, ICU LOS, LOS, and incidence of VAP in mechanically ventilated patients. However, these findings should be interpreted with caution due to the moderate-to-low quality of evidence and the limited number of available studies. Further high-quality, large-scale research is needed to confirm the effectiveness and safety of nurse-led weaning protocols in diverse clinical settings.Systematic review registrationIdentifier: CRD42023487455, https://www.crd.york.ac.uk/prospero.